Discrimination of Soil Types in Southern Kuwait Using Remote Sensing Classification Techniques on Landsat 8 ETM+ Satellite Images - Al -Azemi, Waleed Khalid (Journal of natural sciences, life and applied sciences, 2017)
This study focuses on satellite data Landsat 8 ETM+ and application of remote sensing techniques to delineate various kinds of soils using digital image processing in the southern part of Kuwait. Southern part of Kuwait comprises desert plains, oil fields, sabkha and wafra farms. In this study, satellite imagery is used to achieve rapidly to the actual soil classification. Considering the inaccessibility of the desert areas, RS is essential to accommodate spatial variability and information. Spatial modeling involves the use of GIS for representation of the conceptual model and performance of simple mathematical computations on the stored GIS object attributes for displaying the results spatially.